Geht‘s von nun bergab? Verkümmert das Ideenmanagement im demografischen Wandel? - Feller, Nina; Börner, R.; Voigt, Kai-Ingo (2010)
LIM::242

Organisational and individual unlearning in identification and evaluation of technologies - Scheiner, Christian; Baccarella, Christian; Feller, Nina; Voigt, Kai-Ingo; Bessant, John (International Journal of Innovation Management, 2016)
The ability of an organisation to recognise and evaluate technologically relevant information can be impeded by outdated processes, structures and knowledge. Organisations need therefore a capacity for "intended memory loss", which has been labelled as unlearning. Although a number of scholars have examined unlearning, research is still only beginning to understand unlearning especially in the area of technology identification and evaluation. The goal of this study is therefore to examine unlearning on an organisational and individual level in this context. Unlearning on an organisational level comprises team composition strategies and directives as well as the implementation of unlearning mechanisms. On an individual level, unlearning highlights cognitive prototypes which exert an influence on the perception of technologies and their evaluation. A qualitative approach has been chosen to examine those aspects, in which technological gatekeepers serve as sample subjects. Technological gatekeepers take a crucial role in the technology identification and evaluation as decision makers and due to their influence on organisational structures and processes. The results of this study suggest that unlearning plays currently only a minor role on an organisational and individual level, which is mainly caused by existing rigidities and in the missing understanding of the necessity to unlear

Organizational and Individual Unlearning in Identification and Evaluation of Technologies - Scheiner, Christian; Feller, Nina; Baccarella, Christian; Bessant, J.; Voigt, Kai-Ingo (Technology, Innovation and Entrepreneurship (TIE) Conference, 2015)
LIM::326

Perspectives of Human Resource Management - Sociodemographic Changes at Determinantes of Innovation Behaviour - Voigt, Kai-Ingo; Feller, Nina; Scheiner, Christian (International Conference on Advanced Management Perspectives in Asia (ICAMPA), 2010)
LIM::230

The Impact of Demographic Change on Idea Management - Voigt, Kai-Ingo; Feller, Nina; Scheiner, Christian (Academy of Innovation and Entrepreneurship (AIE) Annual Conference, 2010)
LIM::228